Neuromyelitis Optica: Atypical Clinical and Neuroradiological Presentation. Issue 1 (February 2015) - Splendiani, Alessandra; Mariani, Silvia; Anselmi, Monica; Catalucci, Alessia; Di Cesare, Ernesto; Gallucci, Massimo
The extreme variability of clinical and MRI findings in the suspicion of Devic's disease always requires the detection of specific antibodies (AQP4). MRI scans were performed with a high-field MRI scanner (1.5T General Electric Signa Horizon): the MRI protocol of the brain employed axial DP, T2, T1, FLAIR and DWI weighted images (wi) and coronal T2-wi. After intravenous administration of contrast medium axial and sagittal T1-weighted images of the brain were repeated. The spine protocol employed after contrast medium included sagittal T2-wi, T2-wi with fat suppression and T1-wi. In May 2004, a 64-year-old healthy Caucasian woman began to suffer loss of motor and thermal sensitivity in the left lower limb. MRI showed nonspecific areas of abnormal signal intensity on the deep left frontal and right frontoparietal white matter with no pathological enhancement after contrast medium and a small intramedullary area of altered signal at metameric level C2–C4 with a diagnosis of post-viral transverse myelitis. The patient had two similar episodes years later so the neurologist decided to search for circulating IgG AQP4 with the definitive diagnosis of neuromyelitis optica. In this case, compared to a clinical presentation of atypical deficit neurological involvement, the neuroradiological results of a progressive diffuse involvement of the white matter were atypical.